The Georges Pompidou University Hospital Clinical Data Warehouse: A 8-years follow-up experience. (June 2017) - Jannot, Anne-Sophie; Zapletal, Eric; Avillach, Paul; Mamzer, Marie-France; Burgun, Anita; Degoulet, Patrice
Highlights: Georges Pompidou University Hospital CDW is a key facilitator for research. We describe 74 CDW projects evaluated by the ethics committee between 2011 and 2015. Important methodological support from the medical informatics department was needed. Abstract: Background: When developed jointly with clinical information systems, clinical data warehouses (CDWs) facilitate the reuse of healthcare data and leverage clinical research. Objective: To describe both data access and use for clinical research, epidemiology and health service research of the "Hôpital Européen Georges Pompidou" (HEGP) CDW. Methods: The CDW has been developed since 2008 using an i2b2 platform. It was made available to health professionals and researchers in October 2010. Procedures to access data have been implemented and different access levels have been distinguished according to the nature of queries. Results: As of July 2016, the CDW contained the consolidated data of over 860, 000 patients followed since the opening of the HEGP hospital in July 2000. These data correspond to more than 122 million clinical item values, 124 million biological item values, and 3.7 million free text reports. The ethics committee of the hospital evaluates all CDW projects that generate secondary data marts. Characteristics of the 74 research projects validated between January 2011 and December 2015 are described. Conclusion: The use of HEGP CDWs is a key facilitator for clinical research studies. It required however important methodological and organizational support efforts from a biomedical informatics department.